Tattoos [compact disc] - Gilbert, Brantley (Valory, 2024)
Multi-platinum country rocker Brantley Gilbert readies his seventh studio album. As a writer and producer on all ten tracks, the album embodies his ability to capture the gritty realism of life: from the hustle to provide and protect your loved ones to the profound and poignant moments of love, loss and self-reflection. The project's lead single "Over When We're Sober" with Ashley Cooke is climbing the charts at Country radio after being most added upon its debut.